ANALISIS KEMAMPUAN GURU DALAM PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL PADA MASA ADAPTASI KEBIASAAN BARU DI SDN 105377 NAGA KISAR KEC. PANTAI CERMIN T.A 2020/2021 - Nainggolan, Maria Friska; Girsang, Mei Lyna; Shalihat, Hilma Mithalia; Tampubolon, Heppy Theresia (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2021)
The purpose of the research is to determine the ability of elementary school teachers using digital learning media during the new habit adaptation at State Elementary School 105377, Naga Kisar Pantai Cermin in 2020/2021 academic year. This study is descriptive quantitative research. The sample in this study was 8 teachers. The data collection technique used in this research is questionnaires. The results showed that the teacher's ability using digital learning media at State Elementary School 105377 Naga Kisar was moderate with an average score 3.11. With the percentage of alternative answers for each sub-indicator, the sub-indicator of teachers knowing and being able to use digital learning media, the answers are always 67.18% included in good category, frequent answers 20.31% included in low category, 12.5% answers sometimes, included in very low category. The sub-indicators of digital learning media can build cooperation and confidence of children, 50% of the answers are always included in medium category, 20.83% of the answers are often, low category, the 29.16% answers are sometimes included in low category. The sub-indicators of digital learning media are able to arouse children's enthusiasm and motivation in learning, 7.5% answers are always included in low category, 22.5% answers are often included in low category, sometimes 70% included in good category. Based on the analysis of questionnaire for each sub-indicator, it can be concluded that teacher's ability to use digital learning media at State Elementary School 105377 Naga Kisar is in medium category.